Social network characteristics and well-being in Italy: insights from the PHRASI Study - Berselli, Nausicaa; Caminiti, Marta; Ancona, Angela; Stacchini, Lorenzo; Gallinoro, Veronica; Catalini, Alessandro; Cosma, Claudia; De Nicolò, Valentina; Mazza, Clara; Minutolo, Giuseppa; Cedrone, Fabrizio; Gianfredi, Vincenza (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. Mental well-being should be prioritized in public health as it represents a valuable resource for individuals andcommunities, influencing behavior, social cohesion and social inclusion. The support individuals receive from their social networkscan have a significant impact on mental well-being. This study used data from the Public Health Residents’ Anonymous Survey inItaly, a nationwide cross-sectional survey. The objective was to assess the level of well-being among the Public Health Residentsand investigate the association between the social network characteristics and the well-being in this population.Study design. The current cross-sectional study targeted 1,600 public health residents enrolled in various Italian public healthspecialization schools between June 14 and July 26, 2022.Methods. Participants self-reported both functional and structural characteristics of social network. Well-being was assessedusing the WHO-5 well-being index. Linear regression models, adjusted for age and sex, were applied to examine the associationbetween WHO-5 score and social network characteristics.Results. Out of 379 participants, 51.5% reported bad well-being. Those with bad well-being are more likely women, experiencelower peer-to-peer and supervisor support, face higher work-to-private life interference, and less frequently have a partner.Greater peer-to-peer support (β=1.13, 95% CI=0.68; 1.57), and increased supervisor support (β=1.26, 95% CI=0.86; 1.67),were associated with higher levels of well-being. Conversely, higher work-to-private life interference was associated with lowerperceived well-being. Having a partner resulted in a better perceived well-being (β=1.96, 95% CI=0.94; 2.98). In logistic regressionanalysis, higher peer-to-peer support (OR=0.68, 95% CI = 0.55;0.85) greater supervisor support (OR=0.60, 95% CI=0.49;0.74)and having a partner (OR=0.51, 95% CI = 0.32;0.82) were associated with reduced odds of bad well-being. Conversely, increasedWLI was associated with higher odds of bad well-being (OR=1.47, 95% CI = 1.19;1.82).Conclusions. The characteristics of an individual’s social network play a crucial role in her/his well-being and should be consideredboth in personal and professional contexts when aimed to enhance mental well-being in communities.